Mature silkworm powders ameliorated scopolamine-induced amnesia by enhancing mitochondrial functions in the brains of mice. (April 2020) - Nguyen, Phuong; Kim, Kee-Young; Kim, A-Young; Choi, Bo-Hey; Osabutey, Angelina F.; Park, Young Han; Lee, Hyun-Tai; Ji, Sang Deok; Koh, Young Ho
Graphical abstract: Highlight: GS-SMSP has strong cell proliferation and anti-oxidative stress effects. GS-SMSP has a dose-dependent SCO-induced amnesia suppression effect. GS-SMSP increases the activities of MitoComs and GSTs in HT22 cells. GS-SMSP restores reduced MitoComs' activities and ATP amounts in the brains of SCO mice. GS-SMSP increases MitoComs' activities and ATP amounts in the brains of Sal mice. Abstract: The main goal of this study was to elucidate the neuron proliferation and cognition improvement effects of steamed and freeze-dried mature silkworm powders (SMSP). Concentrates of 80% methanol extracts from golden silk-SMSP (GS-SMSP) contained 3.6–4.9 times more phytochemicals and 1.8–3.1 times more antioxidant activities and showed significantly higher mouse hippocampal HT22 neuronal cell proliferation effects than those of white jade (WJ)-SMSP. In addition, GS-SMSP was more effective in suppressing scopolamine (SCO)-induced amnesia in the mice than WJ-SMSP. Furthermore, the suppression of SCO-induced amnesia by GS-SMSP in the mice was dose-dependent. The significantly reduced mitochondrial respiratory complex (MitoCom) activities and ATP amounts in the brains of SCO-injected mice were recovered in the mice supplemented with GS-SMSP. Taken together, the results of this study indicate that enhanced mitochondrial function in the brains of mice supplemented with GS-SMSP was the molecular basis of suppression of SCO-induced amnesia in a rodent model.